THE CONTRIBUTION WOMEN-MORPHOLOGISTS TO THE DEVELOPMENT KIEV ANATOMICAL SCHOOL (TO THE 180TH ANNIVERSARY OF BOGOMOLETS NATIONAL MEDICAL) - Prysyazhnyuk , Larisa; Yanchishin, Andrey; Dzevulska , Irina; Sinitskaya, Alla; Matkivskaya, Ruzhena; Ostapyuk, Lyubov; Kovalchuk, Oleksandr (The Ukrainian Scientific Medical Youth Journal, 2021)
Historical experience in the development of science is impossible without taking into account the links with all previous experience of mankind. All medical sciences, including anatomy, have their own history, that is, the entire path of development and improvement. Women scientists have made a great contribution to the development of domestic anatomical science and the Kiev Anatomical School, and they also play an important role in various areas of work of the department and university. The purpose of the work is to highlight the contribution of women morphologists of the Kiev Anatomical School at the main stages of development of Ukrainian anatomical research, to trace trends and directions of their work and contribution to the development of the Kiev Anatomical School. Problem-oriented analysis of historical information sources, archival materials of the Department of Descriptive and Clinical Anatomy of Bogomolets National Medical University. A great contribution to the development of the Kiev Anatomical School was made by women anatomists, who are constantly taking an active part in the organization and conduct of many scientific studies conducted at the current level. In the pre-war and post-war years, the scientific search for the department’s employees was mainly aimed at studying the lymphatic system. Later, the Department of Human Anatomy studied the microcirculatory tract of functionally different organs. And during this period, a number of candidate and doctoral theses were protected by the women of the department. In recent years, a scientific search at the Department of Human Anatomy has been aimed at studying morphological changes in organs in burn disease and the effects of various environmental factors in the body. And in this direction, women of the department work quite fruitfully, defending candidate and doctoral theses. Women of the department take an active part in scientific conferences, symposiums, congresses, co-authors several patents and copyright certificates, monographs, textbooks, made a significant contribution to educational and methodological work, co-authored methodological recommendations for teachers and students. The women of the department have completed a foreign internship and are actively engaged in public work. The scientific and pedagogical work of the women of the department for a significant contribution to the development of health care, many years of conscientious work and high professionalism was awarded government awards, diplomas of the university and the Ministry of Health. The life paths of hardworking purposeful women of the Kiev Anatomical School were overflowing with conscientious work and perseverance towards their work. Their pedagogical achievements, sincere attempts to give deep knowledge to their students, became an example for future generations.